KELAS MENENGAH & KONDISI DELIBERATIF Pertukaran Informasi Kompasianer Pada Masa Kampanye Pilkada DKI Jakarta 2012 dan Pemenuhannya Terhadap Kondisi Deliberatif - Nuswantoro, RANGGABUMI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Jakarta is the locomotive of growth of the middle class in Indonesia. Apart from being the capital of the state (central government), Jakarta is Indonesia's largest business city. Everything started from Jakarta. Including the growth of new consumer class (middle class) as well as lifestyle alluring In relation to this, how the reality of middle-class democracy in Jakarta? The phenomenon of local elections in Jakarta in 2012 showed that. This thesis research mengungkat at least two important things namely First, in case the exchange of information during the election campaign Kompasiana Jakarta in 2012, it is necessary to know more about what information is exchanged by the kompasianer. Second, how the exchange of information during the election campaign kompasianer 2012 Jakarta that meet deliberative condition indicator. From the data generated in research on information exchange and quality kompasianer deliberative condition can be stated that the information exchanged by kompasianer already contained at least some substantive things about deliberative ie starting from 1) offer programs and policies of the candidate for Governor and Vice Governor of Jakarta to tackle the problem public (jam, flood, water, etc.), 2) the character candidate for Governor and Vice Governor of Jakarta, 3) the dynamics koalisis / support a political party of the candidate Governor and Vice Governor of Jakarta, 4) governance Jakarta provincial government, up to 5) the quality of the organizers of the local elections (elections) in Jakarta in 2012. However, in the subsequent measurement of the quality of deliberative conditions found that the quality of middle-class democracy as demonstrated by kompasianer yet either. At least it was indicated by the lack of information and discussion that includes deliberative condition indicator, as a condition of the realization of deliberative democracy. Looking at these results it can be concluded that the middle class is represented by kompasianer, who posted all 106 posts during the election campaign of Jakarta, should be increased democratic capacity.